2004
DOI: 10.1016/j.dsr2.2003.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of ocean color and composition of phytoplankton communities in the North Atlantic, equatorial Pacific and South Pacific

Abstract: Monthly averaged level-3 SeaWiFS chlorophyll concentration data from 1998 to 2001 are globally analyzed using Fourier's analysis to determine the main patterns of temporal variability in all parts of the world ocean. In most regions, seasonal variability dominates over interannual variability, and the timing of the yearly bloom can generally be explained by the local cycle of solar energy. The studied period was influenced by the late consequences of the very strong El Niño of 1997-98. After this major event, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 41 publications
10
104
0
Order By: Relevance
“…However, the low NO x concentrations characteristic of the remote marine atmosphere (on the order 10 pptv or less) will produce substantially smaller SOA yields through this process. Ervens et al (2008) found yields of between 2 and 3% at [C 5 H 8 ]/[NO x ] concentration ratios similar to those found under typical marine conditions with our 1.9 Tg/yr isoprene source (∼30pptv isoprene, ∼10 pptv NO x ). These are close to the 3% yields observed during studies of isoprene SOA production under gas-phase oxidation in low-NO x conditions (Kroll et al, 2006).…”
Section: Impacts On Marine Organic Carbon Aerosolsupporting
confidence: 50%
See 2 more Smart Citations
“…However, the low NO x concentrations characteristic of the remote marine atmosphere (on the order 10 pptv or less) will produce substantially smaller SOA yields through this process. Ervens et al (2008) found yields of between 2 and 3% at [C 5 H 8 ]/[NO x ] concentration ratios similar to those found under typical marine conditions with our 1.9 Tg/yr isoprene source (∼30pptv isoprene, ∼10 pptv NO x ). These are close to the 3% yields observed during studies of isoprene SOA production under gas-phase oxidation in low-NO x conditions (Kroll et al, 2006).…”
Section: Impacts On Marine Organic Carbon Aerosolsupporting
confidence: 50%
“…An increase in the isoprene SOA yield would translate to an increased significance for oceanic isoprene in marine OC. Yields of SOA from in-cloud processing of isoprene oxidation products of up to 42% have recently been observed under elevated NO x ([C 5 H 8 ]/[NO x ] ∼0.05) (Ervens et al, 2008). An upper limit of 0.78 TgC/yr of SOA from the top-down 1.9 Tg/yr isoprene source is obtained by applying the maximum 42% SOA yield globally.…”
Section: Impacts On Marine Organic Carbon Aerosolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an eastbound subsurface water current, equatorial undercurrent (EUC), is also important from the viewpoint of affecting the sinking particle flux along the equator (Hansell et al, 1997). Satellite-based SeaWiFS data and an in-situ data study suggest interannual and seasonal changes in chlorophyll-a in the equatorial region (Dandonneau et al, 2004), and unusually large-scale planktonic blooms occurring under changing ENSO conditions in the western and eastern ends of the study area (Ryan et al, 2002).…”
Section: Study Areamentioning
confidence: 99%
“…Owing to effect of ENSO fluctuations, changes in the diversity of microphytoplankton in the equatorial Pacific (Liu et al, 1996), copepods along the west coast of Baja California, Mexico (HernandezTrujillo, 1999), and fish in the global ocean (Worm et al, 2005) have been widely reported. Since plankton species composition affects the efficiency of the biological carbon pump (Dandonneau et al, 2004), a change in plankton diversity may be reflected in minor changes in AA and HA compositions of settling particles, as revealed by the discriminant analysis. In a few recent studies, changes in AA composition have been attributed to the changes in planktonic diversity (Braven et al, 1995;Petersson and Floderus, 2001;Kalachova et al, 2004;Brucet et al, 2005).…”
Section: Discriminant Analysis Of Aa and Ha Compositionmentioning
confidence: 99%